Evolution of Asset-Backed Securities : A Focus on Different Types of ABS and Their Development in Crises - Macek, Tomáš; Witzany, Jiří, 1966-; Panoš, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
The history of asset-backed securities (ABS) is closely tied to moral hazard, risk misjudgment, and excessive issuance, with their vulnerabilities fully exposed during the 2008 financial crisis. While prior research has largely focused on the 1998–2008 period, it often overlooked structural, legislative, and motivational developments in the years that followed. The hypothesis question addressed whether the share of ABS in global financial markets recovered and reached new highs since the 2008 crisis. This study examines ABS issuance and outstanding volumes from 2000 to 2024 using data from sources such as AFME and SIFMA, supplemented by cross-asset comparisons. A sub-analysis of bank balance sheets from 2010 to 2023 draws on annual reports from six major global banks. The findings indicate that asset-backed securities (ABS) reached new highs in 2019–2020, driven by quantitative easing during the COVID-19 crisis. However, this peak did not reverse the long-term decline in issuance, which resumed post-pandemic. While the US remains the leading issuer, showing some signs of recovery, the EU dramatically lags. Notably, market preferences have shifted toward simpler, transparent, and standardized structures, moving away from complex CDOs and synthetic products of recovery.
Vedoucí práce: Jiří Witzany
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses